Africa needs a new public health order to tackle infectious disease threats (2020)
he SARS-CoV-2 pandemic has revealed that Africa needs a new public health order to be resilient, to adapt, and to cope with 21st-century disease threats. The new order will need strengthened continental and national public health institutions; local manufacturing of vaccines, therapeutics, and diagnostics; attraction, training, and retention of a public health workforce; and fostering of respectful local and international partnerships.